Antibacterial Properties of Snakeskin Inspired PDMS Surfaces Layered with Poly-DL-Lactic Acid Nanosheet - Mohd Danial, Ibrahim; Alyssa Asong, Ananthan; Dayang Salyani, Abang Mahmod; Awang Ahmad Sallehin, Awang Husaini; Ngieng, Ngui Sing; Shunsuke, Nakano; Yuta, Sunami; Pierre, Barroy (2023)
The increment of sterilization resistant bacteria minimizes the effectiveness of disinfectants which leads researchers into studying other means in minimizing bacterial contamination on surfaces. Hence, this study plans to investigate surfaces with the ability to discourage bacterial adhesion and reduces the need for frequent sterilization. This study tested the feasibility of applying snakeskin inspired microstructures onto a polydimethylsiloxane (PDMS) surface to reduce bacterial adhesion and increase its antibacterial properties. In theory, the microstructure of snakeskin is smaller or about the same size as a bacterium making it unfeasible for bacterial adhesion. The embeddedelastomeric stamping method was used for the biomimicry of snakeskin onto PDMS surfaces. The replicated snakeskin and controlled (no microstructure) PDMS samples were layered with Poly-DL-lactic acid (PDLLA) nanosheet of different thickness. Then, the morphology of the surfaces was observed using a scanning electron microscope. The surface of the samples was tested with Staphylococcus aureus and Bacillus with compliance of the ISO 22196 standard to evaluate the antimicrobial activity. Our results revealed, surfaces with snakeskin microstructures displayed a 16% reduction in bacterial adhesion compared to flat PDMS. Whereas the presence of nanosheet does not significantly affect the adhesion of bacteria on the replicated snakeskin. These findings suggest that surfaces with the presence of snakeskin microstructures possess antibacterial property.